Dinosaur train. Double feature [videorecording (DVD)] : Dinosaur big city : Dinosaurs A to Z (The Jim Henson Company : PBS Distribution, 2014)
Embraces and celebrates the fascination that preschoolers have with both dinosaurs and trains while sparking an interest in life science, natural history, and paleontology.